Assessment of Students' Knowledge Regarding PTB and Its Causes at Rural Institution of Higher Learning in South Africa - Joseph Neluheni; Joseph M. Mundadi; Takalani R. Luhalima; Thivhulawi Malwela (MDPI AG, 2023)
Background: TB is a significant public health problem around the world, with South Africa being one of the 30 high-burden TB countries, accounting for 87 percent of all estimated incident TB cases. In South Africa, which accounts for 3% of all instances worldwide, research on students' experiences and understanding of underlying factors is lacking. These future leaders are still in a key time of physical and psychological development. This study aimed to test students' understanding of pulmonary tuberculosis (PTB) and its causes at a rural institution of higher learning. Methodology: Quantitative method was used using a cross-sectional design. The study was conducted in the 2020 Vhembe District, Limpopo, South Africa. In the poll, 199 students living in overcrowded campus housing were interviewed. A self-administered questionnaire was used to collect data at the Thohoyandou campus. Data were analysed using version 26.0 of the Statistical Package for Social Sciences (SPSS), with a Spearman's rank-order correlation run. Results: The findings of this study revealed that 25.6 percent of male students and 74.4 percent of female students, respectively, understood PTB, while students at the selected tertiary institution have insufficient awareness of the causes of PTB. The association between education and TB knowledge among the respondents was determined using Spearman's rank-order correlation. There was a statistically significant positive association between education and TB knowledge (Spearman's rho = 0.669, p = 0.035). Conclusions: The study found that students at a higher education institution lacked sufficient general Knowledge regarding PTB. PTB control measures should be adopted to implement better the NSP, NDP, Global STOP TB strategy and the SDGs.